EVALUASI KEBIJAKAN GREEN ECONOMY DI BANJAR KAYUMAS KELOD DENPASAR BALI - Ariyanti, Ni ketut Alit (Jurnal Ilmiah Cakrawarti, 2023)
In the era of transformation 5.0, as it is today, environmental preservation is one of the common problems for people all over the world. All countries need to secure adequate short and long term environmental quality such as natural resources, ecosystems, plant and animal diversity, including the human environment. In the campaign era, green economy campaigns put pressure on businesses that have a high impact on the environment. This also extends to developing countries such as Indonesia, where these environmental threats are sending signals to local governments and their citizens. The method in this research is descriptive qualitative analysis. This qualitative descriptive analysis is used to provide an in-depth and objective description of the research object. Results and discussion of the Green Economy policy at the Kayumas Kelod banjar: 1. The Garbage Bank Program is the concept of collecting and sorting dry waste and having an account book like a bank. The purpose of building a garbage bank is actually not the garbage bank itself. The waste bank is a strategy to build public awareness of the environment and also to be able to 'make friends' with waste to get direct economic benefits from waste. 2. Reforestation, Reforestation activities. carried out to ensure that the quality of the environment is not further degraded and this requires the active participation of the community. Conclusion: Green Economy has a goal to improve social welfare and support the environment and implementing a green economy continues to make breakthroughs